Self-Leadership and Organizational Commitment: Correlation Study of Student Association Members - Poppy Intan Permatasari; Theresia Dewi Setyorini; Femmy Lekahena (Psikostudia : Jurnal Psikologi, 2024)
This study aims to ascertain how self-leadership and organizational commitment among X University student association members relate to one another. The 98 participants in the study's sample were all part of a student organization. The self-leadership scale and the organizational commitment scale are the two scales used in the data collection process. This study is quantitative in nature. The Product Moment Correlation test was used for the analysis. The research hypothesis is supported by the findings of this study, which show a substantial positive relationship between organizational commitment and self-leadership among students in University X (r = 0.475, p = 0.000). The results of additional analysis show that the strategy aspect focusing on behavior has a contribution of 10.81%; the strategy aspect followed by natural rewards is 1.46%, and the strategy aspect is a constructive thinking pattern of 10.29%.Anggota himpunan mahasiswa harus bisa berkomitmen dengan tugas-tugas yang diberikan oleh organisasi. Penelitian ini bertujuan untuk mengetahui hubungan antara self-leadership dengan komitmen organisasi pada anggota himpunan mahasiswa di Universitas X. Sampel dalam penelitian ini adalah seluruh anggota himpunan mahasiswa yang berjumlah 98 orang. Pengambilan data menggunakan dua skala yaitu skala self-leadership dan skala komitmen organisasi. Penelitian ini adalah penelitian kuantitatif. Analisis dilakukan dengan menggunakan uji korelasi Product Moment. Hasil penelitian ini menunjukkan bahwa ada hubungan positif yang signifikan antara self-leadership dengan komitmen organisasi pada anggota himpunan mahasiswa di Universitas X (r = 0,475, p = 0,000) yang berarti hipotesis penelitian diterima. Hasil analisis tambahan menunjukkan bahwa aspek strategi berfokus pada perilaku memiliki kontribusi sebesar 10,81%, aspek diikuti aspek strategi penghargaan alami 1,46%, dan aspek strategi pola berpikir konstruktif sebesar 10,29%.